Pathogenetic Aspects of the Development and Course of Rhegmatogenous Retinal Detachment against the Background of Proliferative Vitreoretinopathy. Literature Review - J. V. Kudryavtseva; A. N. Semyonov (Oftalʹmologiâ, 2023)
Retinal detachment (RD) is the most serious problem of modern ophthalmology, often leading to a decrease or irreversible loss of visual functions. The literature review is devoted to the latest trends in the study of the mechanisms of development and course of rhegmatogenous retinal detachment (RRD) against the background of proliferative vitreoretinopathy. In the pathogenesis of RD, there are five theories, as well as nine main risk factors for development. It is known that the contact between the retinal neuroepithelium and the retinal pigment epithelium is maintained by physical and metabolic forces, as well as by the friction force of the outer segments of photoreceptors and RPE cells. With synchisis and simultaneous syneresis, vitreous detachment develops, with increased traction forces and the possible development of RRD. Retinal detachment is the most serious problem of modern ophthalmology, often leading to a decrease or irreversible loss of visual functions. The review of the literature is devoted to the latest trends in the study of the mechanisms of development and course of rhegmatogenous retinal detachment against the background of proliferative vitreoretinopathy. In the pathogenesis of RD, there are five theories, as well as nine main risk factors for development. It is known that the contact between the retinal neuroepithelium and the retinal pigment epithelium is maintained by physical and metabolic forces, as well as by the friction force of the outer segments of photoreceptors and RPE cells. With synchisis and simultaneous syneresis, vitreous detachment develops, with an increase in traction forces and the possible development of RRD. The presence of a retinal tear rarely leads to RRD. It has been established that a pronounced traction effect, rather than a through rupture of the retina, is a key factor in the development and progression of RRD. Traction occurs in the course of proliferative vitreoretinopathy and the epiretinal layer of the vitreum remaining in the posterior vitreous detachment. With the development of detachment, damage to the hematoophthalmic barrier occurs, leading to the release of cells into the vitreous cavity that affect the development of PVR (epi-, sub- and intraretinally) with the formation of an epiretinal membrane. At the same time, communication with the choroid is lost, hypoxia and acidosis develop. ERMs formed during retinal detachment include glial cells and their subtypes — fibrous astrocytes, Muller cells, microglia, hyalocytes, RPE cells, fibroblasts and myofibroblasts. However, the leading role in the formation and development of ERM belongs to Muller cells and astrocytes. Also involved in the pathological process of ERM formation are: transforming growth factor β2, fibroblast growth factor, nerve growth factor, vascular endothelial growth factor, platelet growth factor, laminin, fibronectin, thrombospondin-1, osteonectin, transcription factor. Against the background of ROS, one should not forget about the change in the chemical composition of the vitreous body (increased content): serum albumin, transferrin, antithrombin III, α1-antichymotrypsin, α1-antitrypsin, α2-HS-glycoprotein, hemopexin, transthyretin, apolipoprotein A1, and fibrinogen